Collaborative learning, transdisciplinarity and social-environmental management in the Amazon: approaches to knowledge production between academia and society - Athayde, Simone; Bartels, Wendy-Lin; Buschbacher, Robert; Seluchinesk, Rosane Duarte Rosa (Revista Brasileira de Pós-Graduação, 2014)
This article focuses on two experiences involving leader training for collaborative social-environmental management in the Amazon seeking to create approaches to strengthen postgraduate education in its construction of paths to sustainable development. The interdisciplinary and transdisciplinary approaches used were adapted from postgraduate and leadership training programmes offered by the University of Florida. The approach, still under construction, aims at integrating complex social-ecological systems theories and methods with participatory management concepts and experiences, and also elements of collaborative and experiential learning in adult education. Lessons learned point to opportunities and challenges in the joint construction of knowledge by academia and society as an innovative paradigm of education for sustainability in the Amazon, integrating the perspectives and knowledge of different social actors.